Effects of feeding diets containing increasing content of purified lignocellulose supplied by sugarcane bagasse to early-weaned pigs on growth performance and intestinal health - Silva-Guillen, Ysenia Victoria [UNESP]; Almeida, Vivian Vezzoni; Nuñez, Amoracyr José Costa; Schinckel, Allan Paul; Thomaz, Maria Cristina [UNESP] (Elsevier, 2022)
A total of 96 weaned piglets, with mean age of 21 days and initial body weight (BW) of 6.67 ± 0.63 kg, were used in a 42-day experiment to evaluate the effects of supplementation of dietary purified lignocellulose (LNC) on growth performance and intestinal health. Piglets were blocked by initial BW and allotted to one of 32 pens, each pen containing three pigs. Dietary treatments consisted of a corn-soybean meal-based control diet with no added LNC and three dietary inclusion rates (10, 20, and 30 g/kg) of LNC. Average daily feed intake (ADFI), average daily gain (ADG), and gain-to-feed ratio (G:F) were determined over 42 days postweaning. On day 14 postweaning, one pig from each pen was euthanized to determine gastrointestinal tract organ weight, small intestinal morphology, and digesta pH, viscosity, fermentation end-products, and bacterial enumeration. Total tract retention time was measured by adding 10 g/kg ferric oxide in the morning feed on day 42. From day 1–14 postweaning, G:F tended to linearly increase (P = 0.088) as the dietary LNC contents increased. Although increasing the dietary LNC supplementation quadratically increased (P = 0.008) ADFI and tended to quadratically decrease (P = 0.072) G:F from day 30–42 postweaning, overall growth performance was unaffected by the treatments. The weight of the small intestine adjusted for kg of BW on day 14 postweaning increased quadratically (P = 0.041) as the dietary LNC contents increased. Increasing the dietary LNC supplementation linearly increased (P = 0.027) crypt depth and tended to linearly reduce (P = 0.075) villus:crypt ratio in the jejunum. Dietary treatments did not affect total tract retention time as well as pH and viscosity of both cecum and colonic digesta. Increasing the dietary LNC supplementation quadratically increased (P = 0.001) cecal butyrate formation, whereas cecal acetate and propionate concentrations did not differ among treatments. Although ileal counts of Lactobacillus spp. and Escherichia coli were similar among treatments, the pathogenic Clostridium perfringens population exhibited a quadratic decrease (P = 0.041) as the dietary LNC contents increased. These results indicate that feeding pig diets containing up to 30 g/kg purified LNC enhanced gut health through the inhibition of harmful bacteria proliferation and the expansion of butyrate producers, without compromising overall growth performance.
Keywords: Growth rate; Insoluble fiber; Microbiota; Short-chain fatty acids; Weaned pigs